2022
DOI: 10.1001/jamapediatrics.2022.1641
|View full text |Cite
|
Sign up to set email alerts
|

Use of Race in Pediatric Clinical Practice Guidelines

Abstract: guidelines (CPGs) guide medical practice. The use of race in CPGs has the potential to positively or negatively affect structural racism and health inequities.OBJECTIVE To review the use of race in published pediatric CPGs.EVIDENCE REVIEW A literature search of PubMed, Medscape, Emergency Care Research Institute Guidelines Trust, and MetaLib.gov was performed for English-language clinical guidelines addressing patients younger than 19 years of age from January 1, 2016, to April 30, 2021. The study team systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
0
9
1
Order By: Relevance
“…In this context, the inclusion of race and ethnicity was a crude surrogate of the structural and societal factors (racism, access to healthcare, poverty, and quality of care) that may predispose someone to developing obesity or being less responsive to AOMs, as race is not a biological marker but rather a social construct. 31 While none of the baseline characteristics assessed in our study predicted whether adolescent participants achieved ≥5% or ≥10% BMI reduction with liraglutide at week 56, in adults, an exposureresponse analysis of three liraglutide trials found that female sex and a lower baseline BMI were associated with greater weight loss compared with male sex and a higher baseline BMI. 32 The weight loss differences between males and females were partly caused by a higher liraglutide exposure in females compared with males of a similar body weight, while exposure differences attributable to baseline BMI were not associated with meaningful differences in weight loss.…”
Section: Identification Of Patients Most Likely To Favourably Respond...contrasting
confidence: 61%
See 1 more Smart Citation
“…In this context, the inclusion of race and ethnicity was a crude surrogate of the structural and societal factors (racism, access to healthcare, poverty, and quality of care) that may predispose someone to developing obesity or being less responsive to AOMs, as race is not a biological marker but rather a social construct. 31 While none of the baseline characteristics assessed in our study predicted whether adolescent participants achieved ≥5% or ≥10% BMI reduction with liraglutide at week 56, in adults, an exposureresponse analysis of three liraglutide trials found that female sex and a lower baseline BMI were associated with greater weight loss compared with male sex and a higher baseline BMI. 32 The weight loss differences between males and females were partly caused by a higher liraglutide exposure in females compared with males of a similar body weight, while exposure differences attributable to baseline BMI were not associated with meaningful differences in weight loss.…”
Section: Identification Of Patients Most Likely To Favourably Respond...contrasting
confidence: 61%
“…Liraglutide was found to be more effective in reducing BMI by ≥5% and ≥10% compared with placebo regardless of participants' sex, race, ethnicity, age, Tanner (pubertal) stage, glycemic status, severity of depression symptoms, or obesity category at baseline, indicating that it may be a reasonable treatment option for adolescents with obesity irrespective of these characteristics. In this context, the inclusion of race and ethnicity was a crude surrogate of the structural and societal factors (racism, access to healthcare, poverty, and quality of care) that may predispose someone to developing obesity or being less responsive to AOMs, as race is not a biological marker but rather a social construct 31 …”
Section: Discussionmentioning
confidence: 99%
“…This disclosure also prompts researchers to think critically about their rationale for including race and ethnicity because these data have historically been used in discriminatory and biased ways that can lead to inappropriate clinical decisions. 11,36,37 The Results section (Section 4) is consistent with the Results section of the American Heart Association's rubric and underscores the importance of avoiding statements that imply that a person's race and ethnicity caused their health outcomes because racism, rather than race, is the exposure. 38 The Discussion portion of the rubric (Section 5) is designed to help authors move beyond merely identifying inequities and toward consideration of strategies to eliminate them.…”
Section: Contents Of the Equity Rubricmentioning
confidence: 84%
“…clinical decision-making, it is critical that race and ethnicity are interpreted as social constructs and that these findings not be construed to suggest a higher innate susceptibility to infection. [63][64][65]…”
Section: Figure Inclusion and Exclusion Flow Diagrammentioning
confidence: 99%